Review on Cold-Formed Steel Connections. (3rd February 2014) - Lee, Yeong Huei; Tan, Cher Siang; Mohammad, Shahrin; Md Tahir, Mahmood; Shek, Poi Ngian
Abstract : The concept of cold-formed light steel framing construction has been widespread after understanding its structural characteristics with massive research works over the years. Connection serves as one of the important elements for light steel framing in order to achieve its structural stability. Compared to hot-rolled steel sections, cold-formed steel connections perform dissimilarity due to the thin-walled behaviour. This paper aims to review current researches on cold-formed steel connections, particularly for screw connections, storage rack connections, welded connections, and bolted connections. The performance of these connections in the design of cold-formed steel structures is discussed.